Politik ekonomi desentralisasi pengusahaan hutan: studi kasus IPPK di Kabupaten Berau, Kalimantan Timur - Sitorus, S. (Bogor Agricultural University, 2003)
During the New Order era of centralized governance, forest management and exploitation were mostly in the hands of large scale companies, which created huge conglomerates closely related to the ruling power and its cronies. Forestry linked policies ignored the interests of local communities and local businesses, which caused many conflicts, forest degradations and damages as well as increased poverty. In international circles, decentralization and regional autonomy were seen as the best way to achieve a better use of the forest, to the benefit of both local communities and forest conservation. Under the new regional autonomy, the district of Berau released a policy allowing the local communities and local businesses to benefit from the remaining forest resources, the so-called IPPK (Timber Extraction and Utilization Permits). These permits were mostly in the form of small-scale logging concessions of 100 hectare. Intensive field work was carried out to assess the implementation of the IPPK system in the district of Berau. The study showed that so far IPPKs have had an overall negative impact, creating more conflicts and higher rates of forest damage. The IPPK system helped to boost illegal logging and over cutting even in protected forests. Meanwhile, local communities proved unable to secure access over forest resources. In terms of benefit allocation, the local communities got the smallest part of the cake. The biggest parts were trusted by third parties such as free riders and rent seekers, including government officials and village elites. The IPPK policy proved detrimental to government revenue, even though it was meant to boost district income (Pendapatan Asli Daerah-PAD) and communities’ well being. Direct cash distribution to the communities created jealousy among villagers and weakened the social links among the community. Overall, it stimulated an already strong consumptive behavior and jeopardized the last remaining forest resources.